The Effect of Breast Self-Examination (BSE) Class on Knowledge and Practice of Breast Self-Examination among Adolescent Girls - Shinta Novelia; Yenny Aulya; Elsa Regiyanti (KHD-Production, 2021)
According to the World Health Organization (WHO), cancer incidence in 2008 to 2012 was increased from 12.7 million cases to 14.2 million cases. Cancer is the second leading cause of death in the world after cardiovascular disease. It is estimated that in 2030 the incidence of cancer will increase to 26 million people and 17 people die of cancer. This research aimed to determine the effect of BSE classes on knowledge and practice of BSE among female students in Senior High School 104 East Jakarta in 2020. This research was a quantitative study with an analytical survey method with the Quasi Experimental approach. The sample in this study was 30 people. The sampling technique was purposive sampling. The research instrument consisted of questionnaire data and BSE observation sheets. The results of the paired t test found that the effect of BSE Class on BSE Knowledge and Practice among female students where ρ <ά = (0,000 <0.05). There was an effect of BSE Classes on Student’s Knowledge and Practice. Adolescent girls are expected to increase their knowledge about breast self-examination and breast cancer which can be obtained from counseling in the nearest health services, namely about the benefits and how to practice breast self-exam.